Organizational Learning in Cross-Border Acquisitions – Empirical evidence from paper industry - Perttu, Sari (My University, 2012)
During the past thirty years acquisitions have been an interest of many researchers. Still even today, over 80 % of the acquisitions are failing to bring value for the company, and more than a half are actually destroying the value of the company. Companies still continue to engage themselves to acquisitions, and when having acquisition experience it is even more likely that they do so. The main purpose of the study is to identify the possibilities that paper companies have to enhance the learning process in cross-border acquisitions. In theoretical part firstly, the acquisition process, and the affect that the national culture has on it, are outlined. Secondly, the organizational learning in the acquisition process is studied. Previous theoretical work has implied that simultaneous effect of company’s acquisition experience and the performance feedback from previous acquisitions impact on company’s future behavior. Still only few empirical studies are conducted to identify this combined effect of these two different sources of learning. For this reason this study concentrates on these aspects of the organizational learning. Focus is on cross-border acquisitions, thus market experience will be taken into account also. Empirical part of the study concentrates on the paper industry. The study follows a deductive research approach and a qualitative research method was chosen. The data was mainly collected through face-to-face interviews from three different paper companies. Documentation and archival records were also used along with the data collected from interviews. Results of the study indicate that variation in how different experiences affect the acquisition process and its two phases exists, and the effect also depends on how the experience is used. Performance feedback is creating behavior adaptation, and based on the study a deeper look is needed in order to use it as a source of learning. Still it seems that experience and performance feedback affect different parts of the acquisition process simultaneously. Results also indicate that in order to learn more from the acquisition process, it should be more systematic and analytical.
Keywords: Cross-border acquisition; organizational learning; acquisition experience; market experience; performance feedback; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|